Analisis Perjanjian Jual Beli Tanah Yang Berstatus Dijaminkan Kepada Pihak Ketiga Menurut Peraturan Perundang-Undangan Terkait - Olwintra Sitorus; Anita Afriana; Kilkoda Agus Saleh (Hakim: Jurnal Ilmu Hukum dan Sosial, 2024)
Sale and purchase of land agreement is a legal act that involves two provisions, which are the provisions of agreement law and the provisions of agrarian law.. Sale and purchase of land agreement can’t be made privately and might cause disputes in the future. This dispute can cause losses for certain parties so that legal action is needed. The purpose of this research is to understand and examine the validity of the transfer of land rights through sale and purchase agreement related to its status that is guaranteed to third parties and the legal action that can be taken by the land buyer as the disadvantaged party because of the transfer of land and/or building rights through sale and purchase agreement related to its status that is guaranteed to third parties. The research uses a normative juridical approach method with analytical descriptive research specifications. Data collection technique in this research is obtained through literature study which was then analyzed using qualitative juridicial method. The analysis shows that the validity of the transfer of land rights through sale and purchase agreement related to its status that is guaranteed to third parties is invalid. That situation violates the legal terms of the agreement which results in the agreement being null and void. The land buyer as the party who is disadvantaged by these actions can file a legal act which is a civil lawsuit. The existence of a court judgement is a form of legal certainty for the parties in dispute to obtain their rights.